Real-time PCR technique for diagnosing respiratory diseases: miR-155, miR-17, miR-181 expression, and COPD - Abdolreza Mohamadnia; Seyedehnarges Tabatabaee; Parvaneh Safarian; Mohammad Bayat; Abdolah Farhadinasab; Mohammad Hossein Soltani; Shadi Shafaghi; Mohammad Varahram; Mehdi Kazempour Dizaji; Fatemeh Hashtrodi Mahmoudi; Yasamin Khorrami; Atefeh Akbarian; et al. (The Egyptian Journal of Bronchology)
Abstract Background and objective Chronic obstructive pulmonary disease (COPD) is a progressive inflammatory condition with limited noninvasive biomarkers for diagnosis and monitoring. Circulating microRNAs (miRNAs), due to their involvement in inflammation, oxidative stress, and tissue remodeling, offer potential as molecular biomarkers. This study aimed to compare the expression of miR-155, miR-17, and miR-181 in COPD patients versus healthy individuals to assess their diagnostic value. Methods This cross-sectional study enrolled 30 COPD patients and 30 age- and sex-matched healthy controls. Peripheral blood samples were collected in EDTA tubes, and the total RNA was extracted using the RNeasy Midi Kit (Qiagen). cDNA synthesis was performed using the ZIST ROYESH kit, and expression levels were quantified by SYBR Green-based real-time PCR. U6 snRNA served as the reference gene, and expression was calculated using the 2^-ΔΔCt method. Ct ≤ 35 was considered positive. Results miR-181 and miR-155 were significantly upregulated in COPD patients with 2.18-fold and 2.32-fold increases, respectively (p < 0.001). Positive expression was detected in 83.3% and 66.7% of patients, respectively. In contrast, miR-17 was downregulated (0.49-fold; p < 0.001) and positive in only 23.3% of patients compared to 80% of controls. No significant differences in age or sex were observed between groups. Conclusion Distinct expression profiles of miR-155, miR-17, and miR-181 were observed in COPD patients, highlighting their potential as noninvasive biomarkers. miR-181 showed the highest diagnostic sensitivity, whereas miR-17 downregulation may reflect remodeling activity. Combined miRNA profiling could enhance COPD diagnosis and stratification.